Early Childhood Maritime Education in Banyuwangi: School Initiative Amid Policy Absence - Festy Kartika Siwi; Nurbiana Dhieni; R. Sri Martini Meilanie (PG-PAUD Trunojoyo, 2026)
Maritime education holds significant potential in shaping the character of young children, particularly in coastal areas. This study aims to describe the implementation of thematic maritime-based learning at TK Cerdas Banyuwangi and to analyze its contribution to enhancing children’s cultural literacy. Using a qualitative case study approach, data were collected through observation, in-depth interviews, and documentation. The findings indicate that the school has integrated maritime values through various contextual activities such as turtle releases, mangrove planting, beach exploration, and the preservation of local traditions like Sego Golong. The learning process also involves the use of natural loose parts as educational materials within classroom learning centers. These results show that even in the absence of formal curricular support from the government, school-level initiatives can serve as a key driver in fostering love for the sea, environmental awareness, and maritime cultural identity from an early age. This study recommends the development of supportive policies and teacher training to expand similar practices across early childhood education institutions.